Programa de Prepara????o para a Aposentadoria (PPA) do Minist??rio da Sa??de: um estudo explorat??rio Bras??lia/DF - Aguiar, Val??ria Cristina da Silva de (2011)
This study represents an analysis of quantitative Preparing For Retirement Program (PAP) of the Ministry of Health was intended to know the outlook on life would be like the worker after retirement and if the PPA contributes to a quality For this stage of life so we opted for an exploratory study that aims to investigate and reflect on the issue perspective of civil servants from the Ministry of Health, regarding the retirement process. In order to contribute to research in order quanti-qaulitativa exploratory. We conclude that the PPA has helped to improve the quality of life of The Ministry of Health.